Investigating the general effects of different types of toluene exposure on the health of workers: an integrative review of the literature - Ahmed Mohsen Abbas El-Hagrasy; Ramadan Hani Karrout; Alexa Lulu Mcguinness; Tarek Ziyad Assaf Mousa Albutain; Dana Khalifa; Fatema Mohamed Hasan Ali Khalil; Eman Tawash; Maryam Alaradi (BMJ Public Health)
Objectives This integrative review aims to evaluate the available empirical and theoretical literature on the effects caused by different types of occupational toluene exposure on the health of workers. We aim to guide future research, legislation, and guidelines with evidence-based recommendations on toluene exposure.Design An integrative review of the literature.Data sources A systematic search strategy was undertaken across five electronic databases; PubMed, Scopus, Medline, CINAHL and ScienceDirect. Furthermore, grey literature was incorporated through hand-searching databases, Google Scholar, open-access engines and Google Advanced Search tool, among other tools.Eligibility criteria Studies investigating the effects of occupational toluene exposure between 2010 and July 2023 were included. Inclusion criteria included full-text English articles, workers aged 18–65, and studies with co-exposures to benzene, toluene, ethylbenzene and xylene or volatile organic compound if direct findings to toluene were reported. Notable exclusion criteria were non-human studies, pregnant women, paediatric and geriatric populations, and studies addressing toluene abuse and not occupational exposure.Data extraction and synthesis 27 studies met the eligibility criteria and were appraised using the Mixed Methods Appraisal Tool. Data were systematically extracted, guiding the synthesis of various themes, namely acute exposure effects, chronic exposure effects, short-term effects, long-term effects, low-dose effects, high-dose effects and reversible versus irreversible effects.Results The review demonstrated that occupational toluene exposure impacts health differently depending on the nature and context of the exposure. Effects can arise in both acute and chronic scenarios, with outcomes that vary by duration, dose and whether the effects are reversible or irreversible.Conclusions The results demonstrate that toluene exposure can cause a wide range of effects based on the type of occupational toluene exposure. These findings can be used to update current guidelines on the recommended threshold limit for toluene exposure. Furthermore, strategies such as implementing mandatory personal protective equipment, improving ventilation and educating workers on the risks of toluene exposure can be put in place to mitigate the risks.